The Role of Sclerotherapy in Children - Eva J. Soelaeman; Hartati N. Soehardjo; Hadjat S. Digdowirogo (The Indonesian Society for Digestive Endoscopy, 2003)
Introduction: Endoscopic sclerotherapy to control variceal bleeding in adults has been proven to be useful. Complications from this procedure that have been reported include esophageal stricture, perforation, mediastinitis and recurrent bleeding. This procedure has increasingly been used in pediatric patients, thus increasing the incidence of its complications. The purpose of this study: To report the effect of sclerotherapy in variceal bleeding Method: All patients that underwent sclerotherapy since 1989 were included in the study and were followed up until December 1999. We recorded the frequency of injections, recurrent bleeding, and gastropathy. Results: During the last ten years, we have used sclerotherapy in 26 patients. The varices were secondary to intrahepatic portal hypertension. The average age at initial sclerotherapy was 7 years (ranging from 1-12 years). Two patients died following initial sclerotherapy. Nine patients could not be followed up and 17 patients were under monitoring for 2-10 years. Four patients died after 2-8 years of follow up due to the underlying diseases. Complete obliteration of all varices was obtained in 12 cases, minimal residual varices in four and 1 case was unfavorable for injection. Six patients (35.3%) suffered from recurrent bleeding; 4 patients had minimal residual varices (1 year follow up), and 2 patients had complete obliteration (3 years follow up). Gastropathy was found in 6 patients after 12 to 32 sessions of injection. Complications such as perforation or stricture were not found. Conclusions: Sclerotherapy is a very useful technique to control variceal bleeding in children. We found recurrent bleeding and gastropathy in 35.3% patients. Other complications were not found. Keywords: Sclerotherapy, children, endoscopy varices esophagus